Paraoxonase, oxidized low density lipoprotein, monocyte chemoattractant protein-1 and adhesion molecules are associated with macrovascular complications in patients with type 2 diabetes mellitus - Sozer, V.; Himmetoglu, S.; Korkmaz, G. G.; Kaya, S.; Aydin, S.; Yumuk, V.; Hatemi, H.; Uzun, H. (EDIZIONI MINERVA MEDICA, 2014)
Aim. The aim of this paper was to evaluate the association between blood glucose, oxidative stress, inflammation, endothelial dysfunction and paraoxonase activity as contributors to the accelerated atherosclerosis seen in type 2 diabetic patients. Methods. Plasma malondialdehyde (MDA), oxidized LDL (oxLDL), monocyte chemoattractant protein-1 (MCP-1), intercellular adhesion molecule-1 (ICAM-1), and vascular cellular adhesion molecule-1 (VCAM-1) levels and paraoxonase-1 (PON1) activity were measured in sixty type 2 diabetic patients, 30 of whom had macrovascular complications, and 30 controls. Results. Diabetics with macrovascular complications had higher levels of MDA, oxLDL, MCP-1, ICAM-1, VCAM-1 than those without, and the difference was significant for all molecules except for ICAM-1. PON1 activity and ApoA1 levels of the controls were significantly higher than that of the patients while PON1 activity and ApoA1 levels in the patients with macrovascular complications were significantly lower than that in patients without. Ambient plasma glucose concentration showed a significant positive association with plasma MDA, oxLDL, MCP-1, and VCAM, and a significant inverse association with PON1 and ApoA1 in diabetic patients. A significant positive correlation between oxLDL and MDA, a negative correlation between oxLDL and PON1; a significant inverse association between MDA and PON1; a positive correlation between MDA and MCP-1 and VCAM while a negative correlation between PON1 and MCP1 and VCAM were detected in patients. Conclusion. Hyperglycemia might play a significant role in generating increased oxidative stress, and decreased PON1 activity, resulting in elevated oxLDL, MCP-1 and VCAM levels. This might be one of the causal pathogenic factors initiating accelerated atherosclerosis in patients with type 2 diabetes mellitus. The implication of these findings are unclear and therefore further studies are required.
Keywords: Oxidative stress; Aryldialkylphosphatase; Oxidized low density lipoprotein; Chemokine CCL2; Intercellular adhesion molecule-1; IMPAIRED GLUCOSE-TOLERANCE; ENDOTHELIAL DYSFUNCTION; VASCULAR COMPLICATIONS; SERUM PARAOXONASE; MCP-1 PRODUCTION; GLYCEMIC CONTROL; EXPRESSION; PLASMA; VCAM-1; General & Internal Medicine